(untitled) (Research, Society and Development, 2019)
Public works are essential for the provision of goods and services to the population, as well as the rise of economic development. This can be observed by the infrastructure works, which serve as support for the entire productive chain of the country. Brazil faces a major problem in relation to the large number of works that generate negative impacts in several sectors. To do so, it is necessary to review the way in which the public administration conducts its projects, seeking improvements, especially from the planning side. This article presents the current scenario of public works stopped in Brazil, verifying their causes, the sectors most affected and the impacts provoked. It also presents the positioning of the public administration for the resumption of works and possible measures to avoid paralysis. This study was based on a bibliographical survey collected from official public agencies, scientific articles, booklets and books. Given this scenario, this article verified the average values of the public works that are stopped, and what are the values necessary for it to return to the original state. With this came the conclusion of the lack of planning in public operations, which lead to their total paralysis, generates exorbitant expenses to the public coffers.